2022
DOI: 10.1155/2022/6274185
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Outcomes of Internet of Things for Patients with Alzheimer’s Disease/Dementia: A Scoping Review

Abstract: Objectives. We aimed to identify and classify the Internet of Things (IoT) technologies used for Alzheimer’s disease (AD)/dementia as well as the healthcare aspects addressed by these technologies and the outcomes of the IoT interventions. Methodology. We searched PubMed/MEDLINE, IEEE Explore, Web of Science, OVID, Scopus, Embase, Cochrane, and Google Scholar. In total, 13,005 papers were reviewed, 36 of which were finally selected. All the reviews were independently carried out by two researchers. In the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
(346 reference statements)
0
4
0
Order By: Relevance
“…Future studies could consider integrating the continuous or frequent computer-aided swallowing assessment with dysphagia training for those who are at risk, for example, using virtual reality with biofeedback systems [ 34 ]. In the long run, we aim to establish a smart dementia care home by integrating various continuous monitoring systems for dementia-related issues, including dysphagia [ 19 ], wandering [ 35 ] and agitation [ 36 , 37 ], and balance training [ 38 ], through the Internet of Medical Things (IoMT) [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies could consider integrating the continuous or frequent computer-aided swallowing assessment with dysphagia training for those who are at risk, for example, using virtual reality with biofeedback systems [ 34 ]. In the long run, we aim to establish a smart dementia care home by integrating various continuous monitoring systems for dementia-related issues, including dysphagia [ 19 ], wandering [ 35 ] and agitation [ 36 , 37 ], and balance training [ 38 ], through the Internet of Medical Things (IoMT) [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that participants made multiple PCP visits during the intervention period, we opted for a duration of three quarters, equivalent to 9 months. Further, a recent scoping review aiming at identifying and classifying digital tools used in dementia care found that in 86% of studies, the intervention duration was less than 12 months 30 …”
Section: Methodsmentioning
confidence: 99%
“…Further, a recent scoping review aiming at identifying and classifying digital tools used in dementia care found that in 86% of studies, the intervention duration was less than 12 months. 30 The DemTab App comprises multiple components and functions.…”
Section: Setting and Participantsmentioning
confidence: 99%
“…As the memory of the elderly gradually decreases with age, and some may have Alzheimer's disease or dementia, they are often unable to find their way home after going out, resulting in serious consequences of getting lost and going missing [36,37]. When the GPS positioning system is used with a smart home, it can identify the location of the older adults and inform the family before an accident occurs, reducing the risk of older adults getting lost.…”
Section: Daily Living Environment and Quality Of Lifementioning
confidence: 99%